2021
DOI: 10.1186/s13018-021-02387-5
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive internal fixation for unstable pelvic ring fractures: a retrospective study of 27 cases

Abstract: Background This study aimed to evaluate the radiographic and clinical outcomes of anterior subcutaneous internal fixation (INFIX) with or without posterior fixation for the treatment of unstable pelvic fractures. Methods Intraoperative blood loss, operation time, and duration of hospital stay were recorded, and fracture union and postoperative complications were evaluated. The fracture reduction quality was evaluated using the Matta score, pelvic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…INFIX technology has the advantages of shorter procedure time, limited soft tissue trauma and reduced blood loss. When establishing subcutaneous channels, the incidence of soft tissue traction injury and thrombosis can be signi cantly reduced, avoiding disruption of blood supply to the fracture site during operation, which is conducive to enhance postoperative healing [23] ; There is no need for accurate reduction before operation, and the treatment options for patients with large displacement, and comminuted fractures are more exible and diverse.…”
Section: Discussionmentioning
confidence: 99%
“…INFIX technology has the advantages of shorter procedure time, limited soft tissue trauma and reduced blood loss. When establishing subcutaneous channels, the incidence of soft tissue traction injury and thrombosis can be signi cantly reduced, avoiding disruption of blood supply to the fracture site during operation, which is conducive to enhance postoperative healing [23] ; There is no need for accurate reduction before operation, and the treatment options for patients with large displacement, and comminuted fractures are more exible and diverse.…”
Section: Discussionmentioning
confidence: 99%
“…In the course of disease treatment, we found that patients with posterior pelvic ring injury treated with PMISS often developed anemia. It would affect postoperative functional recovery and increase mortality [ 11 ]. Although anemia was closely related to surgical trauma and visible bleeding [ 12 ], it was also crucial to pay attention to hidden blood loss (HBL).…”
Section: Introductionmentioning
confidence: 99%